Gender-specific association of alexithymia and norepinephrine/cortisol ratios. A preliminary report - Spitzer, Carsten; Brandl, Stephan; Rose, Hans-Joachim; Nauck, Matthias; Freyberger, Harald J. (Journal of psychosomatic research, 2005)
Alexithymia and posttraumatic stress disorder (PTSD) might share a neuroendocrine pattern characterized by increased urinary norepinephrine (N) and decreased cortisol (C) levels, resulting in a high N/C ratio, at least among male alcoholics. We aimed to explore if this association can also be found in other populations. Twenty-four-hour urine samples were obtained from 12 major depressive disorder (MDD) patients and 23 healthy controls (HC) and tested for N and free C. Participants completed the 20-item Toronto Alexithymia Scale (TAS) and the Symptom Check List (SCL). Controlling for depression, the neuroendocrine parameters did not differ between the MDD and HC participants nor between women and men. The TAS was not associated with N, C or the N/C ratio in the MDD and HC participants nor in females alone. However, in men, the N/C ratio correlated significantly with the TAS ( r=.80). Our preliminary findings indicate that alexithymia is associated with an increased noradrenergic activity and a decreased basal activity of the hypothalamic–pituitary–adrenal (HPA) axis among men. This gender difference may reflect divergent underlying neurobiological processes of alexithymia in men and women.